Patient-reported Outcomes After External Beam Radiotherapy With Low Dose Rate Brachytherapy Boost vs Radical Prostatectomy for Localized Prostate Cancer: Five-year Results From a Prospective Comparative Effectiveness Study. Issue 6 (25th December 2022) - De, Brian; Pasalic, Dario; Barocas, Daniel A.; Wallis, Christopher J. D.; Huang, Li-Ching; Zhao, Zhiguo; Koyama, Tatsuki; Tang, Chad; Goodman, Michael; Hamilton, Ann S.; Wu, Xiao-Cheng; Paddock, Lisa E.; et al.
Abstract : Purpose: Data comparing radical prostatectomy and external beam radiation therapy with low dose rate brachytherapy boost are lacking. To better guide shared decision making regarding treatment, we compared patient reported outcomes through 5 years following radical prostatectomy or external beam radiation therapy with low dose rate brachytherapy boost for localized prostate cancer. Materials and Methods: From 2011-2012, men aged <80 years with localized prostate adenocarcinoma were enrolled and followed longitudinally. Patient reported outcomes included the Expanded Prostate Index Composite. Regression models adjusted for baseline scores and covariates were constructed. Results: The study population included 112 men treated with external beam radiation therapy with low dose rate brachytherapy boost and 1, 553 treated with radical prostatectomy. Compared to radical prostatectomy, external beam radiation therapy with low dose rate brachytherapy boost was associated with clinically meaningful worse urinary irritative/obstructive (adjusted mean score difference [95% confidence interval]: 5.0 [−8.7, −1.3]; P = . 008 at 5 years) and better urinary incontinence function (13.3 [7.7, 18.9]; P < . 001 at 5 years) through 5 years. Urinary function bother was similar between groups ( P > . 4 at all timepoints). Treatment with external beam radiation therapy with low dose rate brachytherapy boost was associated with worse bowel function (−4.0 [−6.9, −1.1]; P = . 006 at 5 years) through 5 years compared to radical prostatectomy. Treatment with external beam radiation therapy with low dose rate brachytherapy boost was associated with better sexual function at 1 year (12.0 [6.5, 17.5]; P < . 001 at 1 year) compared to radical prostatectomy, but there was insufficient evidence to reject the supposition that no difference was seen at 3 or 5 years. Conclusions: Compared to radical prostatectomy, external beam radiation therapy with low dose rate brachytherapy boost was associated with clinically meaningful worse urinary irritative/obstructive and bowel functions but better urinary incontinence function through 5 years after treatment. These patient-reported functional outcomes may clarify treatment expectations and help inform treatment choices for localized prostate cancer.